1997
DOI: 10.1364/ao.36.009152
|View full text |Cite
|
Sign up to set email alerts
|

Fingerprint input based on scattered-light detection

Abstract: The principles of fingerprint imaging are based on scattered-light detection, and the technique is proposed for a compact input device. Light enters a glass plate from its edge and propagates inside the plate by repeating the total internal reflection at the boundaries with air. The ridges of a finger pressed onto the plate scatter the light, which then leaks out of the plate. This scattered light is imaged by an array of gradient-index optical fibers and an image sensor. A prototype sensor has been developed:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 2 publications
0
15
0
Order By: Relevance
“…A fingerprint sensor based on scattered light detection 4 should be able to detect information about the blood movement inside a finger more clearly. Its configuration is illustrated in Fig.8 (a).…”
Section: Sensor Based On Scattered Light Detectionmentioning
confidence: 99%
“…A fingerprint sensor based on scattered light detection 4 should be able to detect information about the blood movement inside a finger more clearly. Its configuration is illustrated in Fig.8 (a).…”
Section: Sensor Based On Scattered Light Detectionmentioning
confidence: 99%
“…The light scattered by the fingers escapes the light-guide and a camera placed nearby capture an image of the fingers. The same principle was used to acquire a fingerprint (Fujieda and Haga 1997). Kurita et al (2005) demonstrated a pointing device by using a fingerprint sensor, where finger deformation provided the displacement information.…”
Section: Introductionmentioning
confidence: 99%
“…Blob in current paper means a closed area in video frame that consist of adjacent pixels and meets predefined criteria's concerning: brightness, color, minimum and maximum size. Usually the blobs in video frame represent images of LED's (very bright and sharp spots) or touch points in systems based on frustrated total internal reflection (FTIR), a technique that comes from biometrics, where it is used for fingerprint image acquisition [9]. Blob detection means finding those areas in the image and creating a list of them with parameters (e.g.…”
Section: Introductionmentioning
confidence: 99%